The potential therapeutic effects of curcumin on pregnancy complications: Novel insights into reproductive medicine. Issue 12 (27th October 2020) - Ghaneifar, Zahra; Yousefi, Zahra; Tajik, Fatemeh; Nikfar, Banafsheh; Ghalibafan, Fatemeh; Abdollahi, Elham; Momtazi‐Borojeni, Amir Abbas
Abstract: Pregnancy complications including preeclampsia, preterm birth, intrauterine growth restriction, and gestational diabetes are the main adverse reproductive outcomes. Excessive inflammation and oxidative stress play crucial roles in the pathogenesis of pregnancy disorders. Curcumin, the main polyphenolic compound derived from Curcuma longa, is mainly known by its anti‐inflammatory and antioxidant properties. There are in vitro and in vivo reports revealing the preventive and ameliorating effects of curcumin against pregnancy complications. Here, we aimed to seek mechanisms underlying the modulatory effects of curcumin on dysregulated inflammatory and oxidative responses in various pregnancy complications.